Evaluasi Rencana Pembelajaran Semester dan Modul Pembelajaran Mata Kuliah Praktikum Pengolahan Sinyal - Fikra Ihsanul Fahmi; Riki Mukhaiyar (Jurnal Pendidikan Teknik Elektro, 2020)
This study aims to review, to identify and reveal problems and the achievement of learning objectives in the Semester Learning Plan and Signal Processing Practicum Subjects Learning Module using the CIPP evaluation model. The research method used is quantitative methods and qualitative methods with descriptive data. Data collection techniques on quantitative methods are taken from filling out questionnaires and qualitative methods using interviews. The data analysis technique used for quantitative data is to tabulate the data against the questionnaire and calculate the score based on the data that has been obtained, while the qualitative data analysis uses data analysis according to Miles and Hubberman. The results of the study concluded that the semester learning plan and the learning module used in the Signal Processing Practicum course using the CIPP evaluation model were overall in a fairly good category. From the use of the CIPP Evaluation model, the Semester Learning Plan and the learning module are feasible to be applied and used again in practicum learning by paying attention to some of the problems found.